Neuroscience-based relational art therapy and deep brain reorienting in the treatment of dissociative identity disorder - Gerge, Anna; Rudstam, Gabriella; Söndergaard, Hans Peter (Frontiers in Psychology, 2025)
Art therapy (AT) has been proposed as a treatment for post-traumatic conditions, potentially by providing somatic sensory input that can (i) enhance the client’s sense of self and embodiment, (ii) modulate arousal, and (iii) aid in rethinking and reframing traumatic memories. However, evidence supporting AT as a treatment for dissociative disorders remains limited. The theoretical basis for the efficacy of AT is discussed in relation to findings regarding the traumatized person’s brain and mindset, as well as its altered functional network connectivity. It is crucial to consider specific alterations in brain networks associated with trauma, particularly those occurring in the deep brain regions, which include the midbrain, the brainstem, and the cerebellum. The hypothesis suggests that early or severe trauma can impair the brain’s higher regulatory functions, as explained by the cascade theory. This theory explains how diverse activation patterns within the midbrain’s periaqueductal gray (PAG) of the midbrain influence the limbic system and cortices, thereby modulating states of being and behavior. Phase-specific, resource-oriented, and long-term therapy for complexly traumatized and dissociative individuals can benefit from novel insights from neuroimaging studies to inform and enhance therapeutic methods. This is illustrated in a clinical vignette with a client diagnosed with dissociative identity disorder (DID), where deep brain reorienting (DBR) was combined with relational AT. The AT component is hypothesized to have facilitated a sense of grounding in the present moment and enhanced the client’s access to her neurophenomenological self. Moreover, changes may have occurred at implicit and non-verbal levels. DBR is believed to have helped the client remain present with her previously avoided and unbearable internal experience. To validate these assumptions, the second author conducted a semi-structured interview that focused on the client’s experiences of being dissociative and in psychotherapy, including the effect of DBR when introduced after AT. The client’s experiences were articulated through a thematic analysis of the interview, which yielded the following themes: Loneliness, getting help, and moving towards togetherness. Further research on and development of therapy methods that enhance the neuroplasticity necessary for highly dissociative clients to change and heal are highly recommended.